2019
DOI: 10.1371/journal.pone.0212321
|View full text |Cite
|
Sign up to set email alerts
|

The knocking down of the oncoprotein Golgi phosphoprotein 3 in T98G cells of glioblastoma multiforme disrupts cell migration by affecting focal adhesion dynamics in a focal adhesion kinase-dependent manner

Abstract: Golgi phosphoprotein 3 (GOLPH3) is a conserved protein of the Golgi apparatus that in humans has been implicated in tumorigenesis. However, the precise function of GOLPH3 in malignant transformation is still unknown. Nevertheless, clinicopathological data shows that in more than a dozen kinds of cancer, including gliomas, GOLPH3 could be found overexpressed, which correlates with poor prognosis. Experimental data shows that overexpression of GOLPH3 leads to transformation of primary cells and to tumor growth e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 95 publications
3
19
0
Order By: Relevance
“…Very strikingly, altered expression of GOLPH3 and Myosin-18A are associated with a range of malignant phenotypes including tumour secretion (41), increased trafficking to the leading edge of migratory cells and consequently augmented cell motility, loss of cell-cell adhesion and invasion (39,45,49,50,(218)(219)(220)(221)(222)(223)(224)(225). However, while this model is strongly supported by a wealth of experimental data, there is at least one report indicating that Myosin-18A is neither localised to the Golgi nor required for its characteristic ribbon like structure (226).…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
“…Very strikingly, altered expression of GOLPH3 and Myosin-18A are associated with a range of malignant phenotypes including tumour secretion (41), increased trafficking to the leading edge of migratory cells and consequently augmented cell motility, loss of cell-cell adhesion and invasion (39,45,49,50,(218)(219)(220)(221)(222)(223)(224)(225). However, while this model is strongly supported by a wealth of experimental data, there is at least one report indicating that Myosin-18A is neither localised to the Golgi nor required for its characteristic ribbon like structure (226).…”
Section: Golph3 -A Golgi Pi4p Effector and Oncoproteinmentioning
confidence: 99%
“…Similar results were obtained by inhibiting YB1 using specific siRNA or by using INK128, an inhibitor of both mTOR complexes (mTORC1/2) [14]; in both cases, artificially increasing the GOLPH3 levels alone had no effects on cell motility, showing that the mTOR-YB1 pathway was pivotal for GBM invasiveness. Recently, Arriagada and co-workers [63] reported that knocking down GOLPH3 through RNAi can deeply alter the cell morphology of a T98G cell line of GBM. This occurs because of the actin cytoskeleton rearrangement and the reduction and dynamics of focal adhesions, which in turn affect both their motility and invasive behavior.…”
Section: Golph3 Deregulation and Brain Tumorsmentioning
confidence: 99%
“…Increasing evidence shows that GOLPH3 is overexpressed in different types of human tumors, including glioblastoma multiforme (GBM) [ 32 , 34 , 35 , 36 ]. Likewise, human glioma cell lines such as A172, U87, U118, U251, and T98G cells overexpress GOLPH3 [ 32 , 35 , 37 ]. Moreover, overexpression of GOLPH3 in these cell lines results in increased cell migration and cell invasion [ 32 , 35 , 37 ], which are hallmarks of oncogenic transformation [ 38 ].…”
Section: Resultsmentioning
confidence: 99%